Action learning: how can it contribute to a collaborative process of pedagogical action research?. Issue 2 (15th March 2021) - O'Siochru, Cathal; Norton, Lin; Pilkington, Ruth; Parr, Elizabeth; Anderson, Babs; Maslen, Joseph
ABSTRACT: This paper explores the processes and outcomes of an action research project, which utilised action learning sets to explore the experiences of a community of academics, who promote pedagogical enhancement in a UK university. Five academics acted as participant action researchers in a longitudinal study exploring the issues they face within their community of practice. Action learning sets were used as the forum through which the participants could discuss the issues they face. The result is an interwoven fabric of action learning and action research, with participants utilizing their reflections on the action research process itself as a catalyst to achieve greater insight into the issues they sought to address through their action learning. This paper explores the themes that emerged from these reflections: choosing between seeking 'solutions' versus promoting discussion in the action learning sets, the complementarity of action research and action learning, the challenges of a collective mode of inquiry. Ultimately, we offer up the process of incorporating action learning sets within an action research project as a participatory approach that can engage colleagues in different roles to reflect on pedagogical practice. Our findings demonstrate both the potential benefits and challenges inherent in combining action learning and action research.